(untitled) (Research, Society and Development, 2021)
This study aimed to analyze the challenges faced by the indigenous population in accessing health care. This is a study of the type of integrative literature review (ILR) by the method of Ganong (1987), which proposes a process of systematization and analysis of data, aiming at the understanding of the subject under study. We enrolled 11 articles from SciELO and LILACS databases, complete with the theme of how the indigenous population faces difficulties in access to health care. The main difficulties faced by the indigenous population are: the length of stay in the support homes or when there is a need for hospitalization; the disruption of their diet, because in the village it is based on food derived from hunting and fishing; difficulties in making appointments and in moving from where they live to the indigenous support home; there are difficulties after receiving care or necessary procedures, because they end up buying drugs with their own financial resources and do not always have them. As for the assistance given by the nursing team, we noticed that they were not prepared to deal with the customs and cultural issues of these people; however, many indigenous people showed satisfaction with the care they received. The present study showed that indigenous people still face great challenges, especially regarding the cultural factor, because they still suffer with the access to health care and the interaction between indigenous and non-indigenous professionals, due to the high turnover. Despite these observations, some studies show that professionals have facilitated the access to health care facilities and their stay at the support site.